RNA pathogenesis via Toll-like receptor-activated inflammation in expanded repeat neurodegenerative diseases - Richards, Robert I.; Samaraweera, Saumya; van Eyk, Clare; O'Keefe, Louise V.; Suter, Catherine (Frontiers in Molecular Neuroscience, 2013)
Previously, we hypothesized that an RNA-based pathogenic pathway has a causal role in the dominantly inherited unstable expanded repeat neurodegenerative diseases. In support of this hypothesis we, and others, have characterized rCAG.rCUG100 repeat double-strand RNA (dsRNA) as a previously unidentified agent capable of causing pathogenesis in a Drosophila model of neurodegenerative disease. Dicer, Toll, and autophagy pathways have distinct roles in this Drosophila dsRNA pathology. Dicer dependence is accompanied by cleavage of rCAG.rCUG100 repeat dsRNA down to r(CAG)7 21-mers. Among the “molecular hallmarks” of this pathway that have been identified in Drosophila, some [i.e., r(CAG)7 and elevated tumor necrosis factor] correlate with observations in affected people (e.g., Huntington’s disease and amyotrophic lateral sclerosis) or in related animal models (i.e., autophagy). The Toll pathway is activated in the presence of repeat-containing dsRNA and toxicity is also dependent on this pathway. How might the endogenously expressed dsRNA mediate Toll-dependent toxicity in neuronal cells? Endogenous RNAs are normally shielded from Toll pathway activation as part of the mechanism to distinguish “self” from “non-self” RNAs. This typically involves post-transcriptional modification of the RNA. Therefore, it is likely that rCAG.rCUG100 repeat dsRNA has a characteristic property that interferes with or evades this normal mechanism of shielding. We predict that repeat expansion leads to an alteration in RNA structure and/or form that perturbs RNA modification, causing the unshielded repeat RNA (in the form of its Dicer-cleaved products) to be recognized by Toll-like receptors (TLRs), with consequent activation of the Toll pathway leading to loss of cell function and then ultimately cell death. We hypothesize that the proximal cause of expanded repeat neurodegenerative diseases is the TLR recognition (and resultant innate inflammatory response) of repeat RNA as “non-self” due to their paucity of “self” modification.